APLIKASI AUGMENTED REALITY UNTUK PENJUALAN PROPERTI SYARIAH BERBASIS ANDROID - Hashfi Ashfahan (2022)
The need to own a house has become a primary need in recent decades. Currently, not only can you buy a house from a banking or conventional mortgage, but you can buy a house through a syariah mortgage without having an interest rate in the payment method. Syariah property is a sale with an Islamic concept and without usury. Islamic Grand Village is a sharia property located in Parung Bogor. Sales in the Islamic Grand Village usually rely on the marketing team and gallery marketing exhibitions. However, Islamic Grand Village does not have a mockup which is one of the most important items when participating in a gallery marketing exhibition due to the high cost of making mockups and low mobility. By building an Augmented Reality model application system, it is hoped that it will become a substitute for mockups. In addition, it is also expected to increase sales innovation from the Islamic Grand Village. The application will be built using the Unity 3D application, the design of the 3D model will be made using the Blender application, and using vuforia as the rest API. Marker Based Tracking method will be used for application development. When the application is made, it is expected that it will not only display 3D objects, but users can perform simple animations on 3D objects.